Pengaruh Perceptions Of Financial Rewards, Work Engagement Terhadap Komitmen Dan Kinerja Karyawan Pada Perusahaan Pelayaran Di Semarang - Adenanthera Lesmana Dewa; Lisda Rahmasari (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
The purpose of this study to analyze the effect of Perceptions Of Financial Rewards (X1), work engagement (X2) to organizationcommitment (Y1) and employeeperformance (Y2). In this study, data were collected through questionnaires to 90 respondents to determine the response of respondents to each variable. Then analyze the data obtained in the form ofquantitative analysis and qualitative analysis. Quantitative analysis include validity and reliability test, the classicassumption test, hypothesis testing via the F test and t test and analysistest, the coefficient of determination (R2). Data analysis techniques used were linear regression analysis that serves to prove the research hypo thesis. The datathat have met the test validity, test reliability, and classical assumption processed so as to produce the followingregression equation: Y1= 0.244X1 + 0.467X2 and Y2 = 0,202X1 + 0,394X2 + 0,209X3 . Results of the analysis with sobel test found that Perceptions Of Financial Rewards (X1), workengagement (X2) has a positive and significant influence on organization commitment (Y1) and Perceptions Of Financial Rewards (X1), work engagement (X2) , Perceptions Of Financial Rewards (X3) has a positive and significant influence on employee performance (Y2) . Hypothesis testing using t-test showed that independent variables found to significantly affect dependent variables.